2009
DOI: 10.1074/jbc.m109.019950
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Status of DJ-1-dependent Activation of Dopamine Synthesis through Interaction of Tyrosine Hydroxylase and 4-Dihydroxy-l-phenylalanine (l-DOPA) Decarboxylase with DJ-1

Abstract: Parkinson disease (PD) is caused by loss of dopamine, which is synthesized from tyrosine by two enzymes, tyrosine hydroxylase (TH) and 4-dihydroxy-L-phenylalanine decarboxylase (DDC).DJ-1 is a causative gene for the familial form of PD, but little is known about the roles of DJ-1 in dopamine synthesis. In this study, we found that DJ-1 directly bound to TH and DDC and positively regulated their activities in human dopaminergic cells. Mutants of DJ-1 found in PD patients, including heterozygous mutants, lost th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 35 publications
(42 reference statements)
5
66
0
1
Order By: Relevance
“…Parkinson's disease, regulates TH and DDC activities: DJ-1 upregulates transcription of the TH gene in a human-specific manner [15] and enhances TH and DDC activities through protein-protein interaction [24]. As in the case of TH, the present study showed that DJ-1 activates VMAT2 expression and enhances its activity at the level of transcription and by protein-protein interaction.…”
Section: Discussionsupporting
confidence: 61%
See 4 more Smart Citations
“…Parkinson's disease, regulates TH and DDC activities: DJ-1 upregulates transcription of the TH gene in a human-specific manner [15] and enhances TH and DDC activities through protein-protein interaction [24]. As in the case of TH, the present study showed that DJ-1 activates VMAT2 expression and enhances its activity at the level of transcription and by protein-protein interaction.…”
Section: Discussionsupporting
confidence: 61%
“…We have reported that DJ-1 positively regulates TH mRNA expression and TH activity by sequestering PSF, a repressor for transcription of the TH gene, and by direct association of DJ-1 with TH, respectively [15,24]. It has been reported that TH and DDC are associated with VMAT2 [3].…”
Section: Association Of Dj-1 With Vmat2mentioning
confidence: 95%
See 3 more Smart Citations